2009
DOI: 10.1088/0264-9381/26/15/155012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the temperature dependence of the mechanical dissipation in thin films of Ta 2 O 5 and Ta 2 O 5 doped with TiO 2

Abstract: Here we report the first results comparing the temperature dependence of the mechanical dissipation in thin films of Ta 2 O 5 and Ta 2 O 5 doped with TiO 2 , of a type suitable for use in the multilayer optical coatings for advanced gravitational wave detectors. The results indicate that doping Ta 2 O 5 with TiO 2 can significantly alter the distribution of activation energies associated with the low temperature dissipation peak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
9
37
0
Order By: Relevance
“…Nevertheless, since only stacks of dielectric layers were deposited, the combined losses can be estimated as follows: . This value is much lower than data already reported, mainly close to a few 10 −4 , for room temperature [21,22,41,44,45] as well as for low temperature [23,44,46]. Although tantala losses dominate in all these results, operating frequencies are typically lower than a few kHz that is significantly lower than a few tens of MHz as demonstrated in the present work.…”
Section: Discussionsupporting
confidence: 46%
“…Nevertheless, since only stacks of dielectric layers were deposited, the combined losses can be estimated as follows: . This value is much lower than data already reported, mainly close to a few 10 −4 , for room temperature [21,22,41,44,45] as well as for low temperature [23,44,46]. Although tantala losses dominate in all these results, operating frequencies are typically lower than a few kHz that is significantly lower than a few tens of MHz as demonstrated in the present work.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, low coating thermal noise is necessary, which can be achieved by reducing coating mechanical loss, reducing coating thickness or by utilizing larger beam sizes on the detector mirrors [14]. Currently, the 2nd generation detectors use coating stacks consisting of alternating layers of silica (SiO 2 ) and tantala (Ta 2 O 5 ), but both materials show increasing mechanical loss when being cooled to low * iain.martin@glasgow.ac.uk temperatures [12,13]. To achieve the ET requirements, coating thermal noise has to be further reduced by reducing the mechanical loss and/or the thickness of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the loss of tantala is temperature dependent [8], and that the temperature dependence of the loss in pure and titania doped tantala coatings is strongly dependent on post-deposition heat-treatment, with several lowtemperature mechanical loss peaks emerging as the heat-treatment temperature is increased [8,9].…”
Section: Introductionmentioning
confidence: 99%